Green tea glycolic extract-loaded liquid crystal systems: development, characterization and microbiological control - Jéssica Bernegossi; Raquel Maria Cunha Barbosa; Patrícia Maciel Rustice; Marlus Chorilli
ABSTRACT Liquid crystal systems (LCSs) have interesting cosmetic applications because of their ability to increase the therapeutic efficiency and solubility of active ingredients. The aim of the present research was to develop green tea glycolic extract-loaded LCSs, to characterize and to perform microbiological control. The ternary phase diagram was constructed using polysorbate 20, silicone glycol copolymer (SGC) - DC 193(r), and distilled water with 1.5% glycolic green tea extract. The systems were characterized by polarized light microscopy. Formulations selected were characterized as transparent viscous systems and transparent liquid system indicated mesophases lamellar structure. The results of the microbiological analysis of mesophilic aerobic microorganisms (bacteria and fungi) revealed that the above formulation showed a biologic load <10 CFU/mL in all samples. In conclusion, liquid crystalline systems that have presented formation of a lamellar mesophases were developed. Furthermore, the formulation and products tested presented the adequate microbiological quality in accordance with official recommendations.